Electrochemical Estimation of the Corrosion Rate of Magnesium/Aluminium Alloys. (22nd November 2009) - Pardo, A.; Feliu, S.; Merino, M. C.; Arrabal, R.; Matykina, E.
Abstract : The corrosion rate of AZ31, AZ80, and AZ91D magnesium/aluminium alloys immersed in 3.5 wt.% NaCl was determined comparing gravimetric and electrochemical measurements. The findings revealed that, for all investigated materials, a fraction of the metallic surface exposed to the corrosive medium did not reveal a normal electrochemical response to the applied signal. This may be associated with phenomena such as partial disintegration of specimens into fine metallic particles, electrochemical formation ofMg + ions, and/or anomalous chemical attack occurring simultaneously with the normal electrochemical corrosion attack. The abnormal electrochemical behaviour was more evident for lower amounts of aluminium in the bulk composition of the investigated materials. Thus, the electrochemical estimates of pure Mg and the AZ31 alloy were not reliable and tended to underestimate corrosion losses.